DAMPAK PENGGUNAAN TEKNOLOGI TERHADAP PENINGKATAN KEUNTUNGAN PELAKU USAHA PENGASAPAN IKAN DI DESA TOOLAWAWO KECAMATAN LALONGGASUMEETO - Nurdiana Azis; Sarini Yusuf (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2017)
Specifically the objectives to be achieved from this research are to find out whether there are impacts and the extent of the impact of the use of technology on increasing profits and the feasibility of the business of smoked fish fumigation. This research was conducted from August to October 2017. Data collection was carried out by direct observation and in-depth interviews with fish smokers. The analysis method used descriptive analysis and profit analysis as well as R/C ratio analysis. The results obtained that the level of profit of business actors increased after using fish fumigation technology amounting to Rp. 5,700,000 per month, compared to before using the technology of Rp. 3,850,000 per month. The business of fish fumigation using smoke house technology is very feasible to be continued with an R/C ratio of 1.7.